PENYELESAIAN SENGKETA DI PERADILAN TATA USAHA NEGARA MELALUI UPAYA ADMINISTRATIF: Prosedur, Sengketa Tata Usaha Negara, Administrasi Pemerintahan - Ahmat Yusuf Al Amin; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2023)
Implementation of the December 4, 2018-issued Republic of Indonesia Supreme Court Regulation (PERMA) Number: 6 of 2018 concerning Guidelines for Settlement of State Administrative Disputes After Pursuing Administrative Actions, which is an additional regulation of the provisions of Articles 75, 76, and 77 of Law Number 30 In Indonesia, a change was made to the state administrative justice system in 2014. The question of whether administrative effort is necessary before bringing state administrative problems before the State Administrative Court is inevitably raised by this change in governance. Second, how do administrative complaints to PTUN get resolved?